New records of atypial coral reef habitat in the Kimberley, Australia - Richards, Zoe; Bryce, M.; Bryce, C. (Hindawi Publishing Corporation, 2013)
New surveys of the Kimberley Nearshore Bioregion are beginning to fill knowledge gaps about the region’s marine biodiversity and the national and international conservation significance of this little-known tropical reef system. Here we report the recent finding of two unique coral habitats documented at Adele Island and Long Reef during the Woodside 2009/2010 Collection Project surveys. Firstly, we report the finding of a subtidal zone of mixed corallith and rhodolith habitat which appears on current records, to be unprecedented in Australia. Secondly, we report the discovery of an atypical Organ Pipe Coral habitat zone and provide empirical evidence that this commercially valuable species reaches an unparalleled level of benthic cover. We provide additional details about the wider hard and soft coral assemblages associated with these unique habitats; discuss the potential biological causes and consequences of them, and make recommendations to benefit their conservation.